The Dipyridamole Added to Dual Antiplatelet Therapy in Cerebral Infarction After First Acute Myocardial Infarction: A Nationwide, Case-Control Study - Wang, Mei-Tzu; Tsai, Cheng Ken; Kuo, Shu-Hung; Huang, Wei-Chun; Lin, Kun-Chang; Hung, Wang-Ting; Cheng, Chin-Chang; Tang, Pei-Ling; Hung, Cheng Chung; Yang, Jin-Shiou; Liang, Hsin-Li; Mar, Guang-Yuan; et al. (Frontiers in Neurology, 2018)
Background and Purpose: No previous study has compared the impact of dipyridamole-based triple antiplatelet therapy on secondary stroke prevention and long-term outcomes to that of dual antiplatelet therapy (DAPT) in patients with acute myocardial infarction (AMI) and previous stroke. This study aimed to evaluate the impact of dipyridamole added to DAPT on stroke prevention and long-term outcomes in patients with cerebral infarction after first AMI. Methods: This nationwide, case-control study included 75,789 patients with cerebral infarction after first AMI. A 1:4 propensity score matching ratio was adopted based on multiple variables. Finally, the data of 4,468 patients included in the DAPT group and 1,117 patients included in the Dipyridamole-DAPT group were analyzed. Primary outcome was overall survival. Secondary outcomes were cumulative event rate of recurrent MI or stroke, and cumulative intracerebral haemorrhage (ICH) and gastrointestinal bleeding rate. Results: Long-term survival rate was comparable between the two groups (log-rank P = .1117), regardless of sex analyses. However, after first year, DAPT subgroup revealed better survival over DAPT-dipyridamole subgroup (log-rank P = .0188). In age subgroup analysis, a lower survival rate was detected in younger patients from the Dipyridamole-DAPT group after first year (log-rank P = .0151), but no survival difference for older patients. No benefit of Dipyridamole-DAPT was detected for patients after AMI, regardless of the myocardial infarction type. DAPT was superior to Dipyridamole-DAPT in patients who underwent percutaneous coronary intervention (PCI) (log-rank P = .0153) and ST elevation myocardial infarction after first year (log-rank P = .0019). Dipyridamole-DAPT did not reduce cumulative event rate of recurrent MI or stroke in patients after AMI. Moreover, Dipyridamole-DAPT increased the cumulative ICH rate (log-rank P = .0026), but did not affect the cumulative event rate of gastrointestinal bleeding. In Cox analysis, dipyridamole did not improve long-term survival. Conclusions: This nationwide study showed that Dipyridamole-DAPT, compared with DAPT, did not improve long-term survival in patients with stroke after AMI, and was related to poor outcomes after one year. Dipyridamole-DAPT did not reduce recurrent rate of MI or stroke, but increased the ICH rate without impacting the incidence of gastrointestinal bleeding.